MANAJEMEN PELAYANAN REHABILITASI SOSIAL DALAM PENANGANAN ANAK JALANAN DI DINAS SOSIAL KOTA SURABAYA - maria ratu mirna; Endang Indartuti (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469))
Surabaya is the second largest city in Indonesia after Jakarta. The population of the city of Surabaya in 2020 is 2. 904 751 people. Along with the dense population caused by the rapid population growth in Indonesia. Poverty is the dominant factor that causes the number of buskers, beggars, homeless people and street children and the government's form of concern for street children is to carry out rehabilitation. The purpose of this study is to determine the management of social rehabilitation services in dealing with street children at the Surabaya City Social Service. This study used qualitative descriptive research with as the type of the research. The results of the study that has been done, so at this writing it can be concluded that: the management of social rehabilitation services in handling street children at the Surabaya City Social Service as seen from the aspect of the rehabilitation services for street children has been going well and, in its implementation, has been optimal. Where street children in the Surabaya City Social Service can take part in any rehabilitation program provided by the Surabaya Social Service.